Pengaruh Pemberian Kompos dan ZPT Nabati dari Ekstrak Jagung Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) - Sandi, Akmalia; Hariyono, Kacung (Berkala Ilmiah Pertanian, 2024)
Tomato (Solanum lycopersicum) is a plant that is widely grown in Indonesia. Market demand for tomatoes is high when compared to other fruit and vegetable commodities. Price instability can be caused by several factors, including decreased crop productivity. Providing nutrition that is considered safe is by using organic materials on agricultural land, which is one solution to the problem of land degradation. Providing compost and vegetable PGR from corn extract are organic additives that are safe to use in cultivation activities. VegetablePGR from corn extract contains the cytokinin hormone which plants need for the growth process. This research was conducted in a Greenhouse located in Martopuro Village, Pasuruan Regency. The experiment was carried out factorially using the basic pattern of Completely Randomized Design (CRD). The observed variables included plant height, leaf area index, percentage of flowers becoming fruit, number of fruit, fruit diameter, fruit weight, vitamin C content. The data obtained through measurements were then analyzed using Analysis of Variance (ANNOVA). If the results of the ANNOVA analysis show significantly different results, it is necessary to carry out further tests using the Duncan Multiple Range Test (DMRT) with a confidence level of 95%. The research results showed that the interaction of compost and vegetable PGR from corn extract showed very significantly different results on plant height variables. The single compost treatment showed significantly different results on the variables of plant height, leaf area index and number of fruit. The single plant PGR factor from corn extract showed significantly different results on the leaf area index variable.